Ordenamento do comércio informal no Projeto Novo Centro: uma experiência de avaliação em profundidade - Mascarenhas, Isídio Nascimento (2022)
The City Hall of Fortaleza, in mid-2018, based on the Municipal Public Policy for Urban Planning, developed a process of reorganizing the street vendors in the city center, based on a project called Novo Centro. The present investigative study called - Informal Commerce Planning in the Novo Centro Project: An In-Depth Assessment Experience, was proposed from our professional experience as an Urban Activities and Sanitary Surveillance Inspector as well as Inspection Manager at AGEFIS - Agência de Fiscalização de Fortress in the downtown area. The study aims to evaluate in depth the Novo Centro Project, based on the planning of informal commerce, carried out on Guilherme Rocha and Liberato Barroso streets, from 2018. The study, in addition to the data collected, through bibliographic and documentary research, sought to raise still, primary data, such as questionnaires, semi-structured interviews and in-depth interviews. The participation of the 360 street vendors who were interviewed through questionnaires stands out. In addition to inspectors, shopkeepers, and managers who also contributed to the process through interviews. This study was developed through a qualitative social research modality with quantitative contributions, circumscribed in tables and graphs. The fieldwork revealed that the result of the project was accepted as satisfactory by most of the subjects involved, but it was evident that the project only reinforced the strength and capitalist interests of local shopkeepers